Pelatihan Teknologi dalam Menggunakan Platform Pembelajaran Digital untuk Meningkatkan Kompetensi Guru - Riskyka; Haryati; Irwanto; Husna Lubis (LPPM STKIP AL MAKSUM, 2021)
Online learning is seen as a solution to continue teaching and learning activities during the corona virus pandemic. Although agreed upon, this approach is controversial. Teachers must be able to teach using effective and efficient learning technology, and in fact there are still many teachers who are not yet skilled in using learning technology, especially in Langkat district. Community Service (PKM) which will be carried out at SMA Negeri 1 Secanggang is an activity to provide training that is focused on introducing Learning Technology that can be used by High School (SMA) teachers. This training is designed to help teachers design Google Classroom learning, hold meetings on Google Meetings or Zoom, help students become independent students with the ability to explore independently, assess student learning outcomes using appropriate applications. Assignments, quizzes, and online exam forms.